Indikator Karakteristik Fisik Rumah Dominan dalam Penentuan Status Kemiskinan untuk Program Rehab Rumah tidak Layak Huni di Kabupaten Sidoarjo - Anita Diyanti Puteri; Hari Basuki Notobroto (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
Poverty is a problem in the construction of the Sidoarjo district. Sidoarjo regency government has conducted several policies in the poverty reduction process. Somethings that should be known by the government in poverty alleviation is the physical characteristics of homes in poor households in the Sidoarjo district. Physical characteristics of the house into one of the house into one of the measures in view of poverty and enable government in the process of poverty reduction policies. This study intended to determine dominant house physical characteristics indicator in poverty status for Unliveable House Rehabilitation Program located in Sidoarjo district. This study was observational with cross sectional design which cross sectional data was describing facts over a time period. The secondary data that being used was 99,492 household in Sidoarjo district from PPLS (2011). Data analyzed bivariabel, followed by multivariabel and logistic regression multinomial. The results showed that the significant variables poverty status is ownership status, roof type and quality, wall type and quality, and fl oor type. The dominant house physical characteristics indicator toward poverty status is fl oor type.